Method for designing and controlling compliant gripper. (August 2016) - Spanu, A R; Besnea, D; Avram, M; Ciobanu, R
Abstract: The compliant grippers are useful for high accuracy grasping of small objects with adaptive control of contact points along the active surfaces of the fingers. The spatial trajectories of the elements become a must, due to the development of MEMS. The paper presents the solution for the compliant gripper designed by the authors, so the planar and spatial movements are discussed. At the beginning of the process, the gripper could work as passive one just for the moment when it has to reach out the object surface. The forces provided by the elements have to avoid the damage. As part of the system, the camera is taken picture of the object, in order to facilitate the positioning of the system. When the contact is established, the mechanism is acting as an active gripper by using an electrical stepper motor, which has controlled movement.